Inter-provincial inequality of public health services in China: the perspective of local officials' behavior - Tianxiang Chen; Ying Wang; Xiaoyi Luo; Yuxuan Rao; Lei Hua (BMC, 2018)
Abstract Background After economic reform, China experienced rising public health services inequality between the eastern developed and mid-west undeveloped provinces. The fiscal transfer payment system which aims to shape the disparities was considered inefficient. However, there are only a few studies that address the political reason when analyzing the inter-provincial public health services inequality. And the previous studies did not consider a possible non-linear relationship between the fiscal transfer payments and the inter-provincial public health services equalization. Methods This paper argues that the local officials' fanatical pursuit of local economic growth which driven by the Political Promotion Tournament and the polarized fiscal self-sufficiency (fiscal capacities) of local governments are responsible for the inter-provincial inequality of public health services and the inefficiency of fiscal transfer payments. By constructing panel threshold regression models with fiscal self-sufficiency of local governments as threshold variable, this study tries to empirically investigate the optimal level of the local governments' self-sufficiency at which the fiscal transfer payments can effectively promote equalization. Results Threshold effects exist between fiscal transfer payments and inter-provincial public health services equalization. The effects on inter-provincial public health services equalization show trends that first increase and then decrease as the fiscal self-sufficiency of local governments increases. And there exist a range of fiscal self-sufficiency between 29.236 and 43.765% or between 28.575 and 45.746% for local governments where the fiscal transfer payments can effectively achieve equalization. Currently, the vast majority of provinces in China remain in the ineffective regime where the fiscal transfer payments are inefficient in shaping inequality. Conclusions This paper explains the reason of inequality in public health services and the inefficiency of fiscal transfer payment system from Chinese local officials' behavior aspect, and try to find out an effective solution by focusing on the local government's fiscal capacity. The effective way to narrow the inequality is to establish a flexible tax-sharing system to adjust local governments' fiscal capacities and give local governments with low fiscal self-sufficiency more fiscal resources. The new policy measures recently launched by Chinese central government coincide with our recommendations.